2005
DOI: 10.1016/j.neuron.2005.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Mental Concerts: Musical Imagery and Auditory Cortex

Abstract: Most people intuitively understand what it means to "hear a tune in your head." Converging evidence now indicates that auditory cortical areas can be recruited even in the absence of sound and that this corresponds to the phenomenological experience of imagining music. We discuss these findings as well as some methodological challenges. We also consider the role of core versus belt areas in musical imagery, the relation between auditory and motor systems during imagery of music performance, and practical impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
209
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(248 citation statements)
references
References 19 publications
28
209
0
4
Order By: Relevance
“…Our results probably refer to processes distinct from those corresponding to an increased activity in the superior temporal gyrus after regular patterns of sound (Hughes et al, 2001;Mustovic et al, 2003), at the offset of long-duration sound (Jäncke et al, 1999;Harms and Melcher, 2002;Seifritz et al, 2002), or induced by a brief period of silence (Kraemer et al, 2005) interpreted as auditory imagery. Auditory imagery has been also shown to increase activity in the auditory areas (Bunzeck et al, 2005;Zatorre and Halpern, 2005) and in the right inferior frontal areas (Hoshiyama et al, 2001). However, two points argue against a role of mental imagery in the observed effect.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our results probably refer to processes distinct from those corresponding to an increased activity in the superior temporal gyrus after regular patterns of sound (Hughes et al, 2001;Mustovic et al, 2003), at the offset of long-duration sound (Jäncke et al, 1999;Harms and Melcher, 2002;Seifritz et al, 2002), or induced by a brief period of silence (Kraemer et al, 2005) interpreted as auditory imagery. Auditory imagery has been also shown to increase activity in the auditory areas (Bunzeck et al, 2005;Zatorre and Halpern, 2005) and in the right inferior frontal areas (Hoshiyama et al, 2001). However, two points argue against a role of mental imagery in the observed effect.…”
Section: Discussionmentioning
confidence: 97%
“…They found high-level areas (including dorsolateral prefrontal areas) partially overlapping the visual attention network (Kanwisher and Wojciulik, 2000;Corbetta and Shulman, 2002) as well as enhanced activity in the auditory areas (Heschl's gyrus and planum temporale) (Woldorff et al, 1993;Downar et al, 2000;Lipschutz et al, 2002). In addition, a recent report (Kraemer et al, 2005) showed that musical gaps can induce auditory activations, likely to be related to musical mental imagery (for review, see Zatorre at al., 2005). In all of these studies, however, the activity was always recorded in the presence of acoustic stimuli and/or scanner noise.…”
Section: Introductionmentioning
confidence: 99%
“…One theory is that regular activation of neural processes associated with voluntary singing (including subvocal) causes involuntary musical imagery experiences to be longer. Such neural areas are already known to overlap with the activity seen in purposeful musical imagery (Halpern & Zatorre, 1999;Hickok et al, 2003;Kleber et al, 2007;Kraemer et al, 2005;Zatorre & Halpern, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…One potential explanation for these findings is that regular activation of neural processes associated with music listening, many of which overlap with activity seen in purposeful musical imagery (Halpern & Zatorre, 1999;Hickok, Buchsbaum, Humphries, & Muftuler, 2003;Kleber, Birbaumer, Veit, Trevorrow, & Lotze, 2007;Kraemer Macrae, Green, & Kelley, 2005;Zatorre & Halpern, 2005), may drive individual characteristics in INMI.…”
mentioning
confidence: 99%
“…In a recent study, Zatorre and Halpern (2005) raised the question as to whether there is evidence that auditory and motor imagery are integrated in the brain. We feel that the current findings provide a preliminary answer.…”
Section: Discussionmentioning
confidence: 99%